Agenda 2030 e o planejamento estratégico dos Programas de Pós-Graduação da Universidade Estadual do Oeste do Paraná (Unioeste): análise das percepções das Coordenações - Tenório, Kristianno Fireman (2024)
This study analyzes the perceptions of the stricto sensu Graduate Programs (PPGs) at the State University of Western Paraná (Unioeste) regarding strategic planning instruments and methods, aiming to make it a more sustainable higher education institution, in alignment with the 2030 Agenda. The importance of Unioeste’s PPGs as development agents in the region is emphasized, committed to driving sustainable socioeconomic growth by fostering highly qualified human capital. The role of universities as a tool for sustainable development is contextualized, utilizing a systematic review to address the question: is the university a tool for sustaining sustainable development? This research is presented as qualitative, descriptive, and applied, with primary data collection through questionnaires administered to program coordinators, including coordinators, vice-coordinators, and secretaries, alongside an analysis of Unioeste’s documents. Content analysis, Likert scale, and systematic review are used as methods to triangulate results within a multimethod analysis. The lack of adherence of the PPGs to the strategic practices for the 2030 Agenda emerged as a critical issue. After interpreting the results and examining each PPG’s delicate perspectives on sustainability and their specific activities, there is a lack of cohesion with the Sustainable Development Goals (SDGs). To strengthen PPG actions in integrating the SDGs, it is recommended to promote SDG-aligned actions and research, establish and strengthen partnerships, define clear and measurable goals, and develop ongoing training. Creating specific metrics and indicators is essential to ensure transparency and effectiveness in implementing the SDGs, contributing to a more sustainable and equitable society.